Experimental evidence of the effect of nutrient enrichment on the zooplankton in a Brazilian coastal lagoon - KOZLOWSKY-SUZUKI,B. (2002)
Non-treated sewage disposal is one of the main impacts to which Imboassica Lagoon has been subjected. The aim of this study was to evaluate the effect of a potential increase in the artificial enrichment on the environmental conditions and zooplankton of this system. To this end, an experimental study was conducted in mesocosms where nutrients were added daily. Bacterial numbers, chlorophyll-a, and picoplanktonic cyanobacteria densities showed an increase with the availability of nutrients. Bacterio- and phytoplankton seemed to be regulated by the rotifers Brachionus rotundiformis and Hexarthra brandorffi.